Is Chinese monetary policy forward-looking? - Chengsi Zhang; Chao Dang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
This paper investigates the empirical validity of the claim that China employed a forward-looking monetary policy rule from 2001 to 2016. Survey expectations are used in conjunction with competing money supply and interest rate rules. The paper contributes to the literature by addressing the problems of serial correlation and structural breaks in the underlying policy reaction function. Un-like earlier studies indicating a strong role for expectations in Chinese monetary policy, we find expectations only began to play a significant role after 2008. This finding is robust for expectations series based on surveys of both households and forecasting experts. We also find that the People's Bank of China promotes economic growth in procyclical fashion, but applies countercyclical policy in managing inflation.
URN:NBN:fi:bof-201802261241
Keywords: E58; E31; 330